Kecenderungan Status Identitas Vokasional Siswa - Ahmad Fajri; Yusi Riksa Yustiana; Amin Budiamin (Journal of Education and Counseling (JECO), 2020)
This study is to determine the tendency of the identity status of class XI students of SMK Negeri 5 Bandung for the 2020/2021 school year. The study used a quantitative approach because it processed data to obtain a tendency for vocational identity of class XI students of SMK Negeri 5 Bandung. In general, it is revealed that students who have achievement identity status in class XI SMKN 5 Bandung are 78.9%, foreclosure identity status 10.8%, moratorium identity status 5.5%, and diffusion identity status 3.9%. Most of the XI grade students of SMKN 5 Bandung have a clear view of the future and are fighting for it and are able to control the exploration process to achieve a commitment.